TAX ADMINISTRATION OF ARGES COUNTY – APPROACHES FROM THE PERSPECTIVE OF HUMAN RESOURCES - Carmen Mihaela MOGOIU; Mariana Luminita LINTA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The implementation of the Romanian Tax Administration Modernization Project (RAMP) and the frequent legislative changes have influenced over the last years the activity and, implicitly, the performance of the National Agency for Fiscal Administration. The Romanian Tax Administration Modernization Project, funded under a loan agreement between Romania and IBRD, has had syncope in its implementation and has not generated the expected results to date. The present paper presents the perception of the Argeş County Public Administration's employees regarding the results of the fiscal administration reform process in Romania, by carrying out a case study of an X-ray of the human resources situation in the field.